2006
DOI: 10.1614/wt-05-034r.1
|View full text |Cite
|
Sign up to set email alerts
|

ALS-Inhibitor Resistance in Populations of Eastern Black Nightshade (Solanum ptycanthum) from Ontario

Abstract: Populations of eastern black nightshade suspected of being resistant to acetolactate synthase (ALS) inhibitors have been reported since 1999 in different locations in Ontario, Canada. This event has threatened the use of ALS inhibitors for control of this species. The objectives of this study were to evaluate the spectrum of resistance to different ALS-inhibiting herbicides and to examine the effectiveness of alternative modes of action herbicides. Growth room experiments were conducted to determine the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…The results of the in vitro ALS activity inhibition assays of HN-02F1-1 plants were consistent with the results of the wholeplant herbicide bioassays. This finding further confirmed that the Ala-205-Val mutation plays an essential role in SU and IMI herbicide resistance, which is similar to the conclusions of other reports (Ashigh and Tardif 2006;Chen et al 2015). Moreover, the HN-02F1-1 plants were highly resistant to TPs; this is the first reported case in which the Ala-205-Val mutation provides resistance to TP herbicides (Tranel et al 2019).…”
Section: In Vitro Assays Of Als Activitysupporting
confidence: 87%
“…The results of the in vitro ALS activity inhibition assays of HN-02F1-1 plants were consistent with the results of the wholeplant herbicide bioassays. This finding further confirmed that the Ala-205-Val mutation plays an essential role in SU and IMI herbicide resistance, which is similar to the conclusions of other reports (Ashigh and Tardif 2006;Chen et al 2015). Moreover, the HN-02F1-1 plants were highly resistant to TPs; this is the first reported case in which the Ala-205-Val mutation provides resistance to TP herbicides (Tranel et al 2019).…”
Section: In Vitro Assays Of Als Activitysupporting
confidence: 87%
“…To increase the safety margin, it will be better if some safeners are developed. The effectiveness of triazine herbicides (atrazine) against Eastern black nightshade ( Solanum ptycanthum ) populations that were resistant to ALS inhibitors (imazethapyr, flumetsulam, cloransulam, nicosulfuron, prosulfuron, and rimsulfuron) was reported by Ashigh and Tardif (2006). Solanum ptycanthum populations resistant to ALS herbicides also were susceptible to chloroacetamide (metolachlor, dimethenamid, and flufenacet).…”
Section: Resultsmentioning
confidence: 99%
“…Metribuzin was found to be effective for the control of isoproturon-R P. minor in wheat but its application timing is narrow, that is, early application can be toxic and delayed application, particularly under untilled conditions without preseeding and an unselective herbicide (glyphosate/paraquat) being less effective (Chhokar et al 2006). To increase the safety margin, it will be better if some safeners are developed.The effectiveness of triazine herbicides (atrazine) against Eastern black nightshade (Solanum ptycanthum) populations that were resistant to ALS inhibitors (imazethapyr, flumetsulam, cloransulam, nicosulfuron, prosulfuron, and rimsulfuron) was reported by Ashigh and Tardif (2006). Solanum ptycanthum populations resistant to ALS herbicides also were susceptible to chloroacetamide (metolachlor, dimethenamid, and flufenacet).…”
Section: Response Of Triazine and Dinitroaniline Against Multiple Hermentioning
confidence: 99%
“…Since 1999, 12 populations of S. ptychanthum from different locations in Ontario have been confirmed R to imazethapyr (Ashigh & Tardif, 2006). A single point mutation coding for Ala 205 Val substitution confers resistance in these populations.…”
Section: Introductionmentioning
confidence: 97%